Scanning proton beam therapy reduces normal tissue exposure in pelvic radiotherapy for anal cancer. Issue 3 (December 2015) - Anand, Aman; Bues, Martin; Rule, William G.; Keole, Sameer R.; Beltran, Chris J.; Yin, Jun; Haddock, Michael G.; Hallemeier, Christopher L.; Miller, Robert C.; Ashman, Jonathan B.
Abstract: An inter-comparison planning study between photon beam therapy (IMRT) and scanning proton beam therapy (SPBT) for squamous cell carcinoma of the anus (SCCA) is presented. SPBT plans offer significant reduction (>50%, P = 0.008) in doses to small bowel, and bone marrow thereby offering the potential to reduce bowel and hemotoxicities.